Analisis Penerapan Sistem Informasi Akuntansi Persediaan Pada PT PLN (Persero) UP3 Ogan Ilir - Masnoni; Zein Ghozali; Hilwa Anggraini; Nelly (JURNAL EKOBIS Kajian Ekonomi dan Bisnis, 2021)
This study aims to analyze the application of inventory accounting information systems used at PT. PLN (Persero) UP3 Ogan Ilir. This type of research is a case study with a descriptive analysis approach. Data collection techniques used consisted of interviews and documentation. The data analysis technique used is a comparative analysis technique. Data from interviews and documentation are compared with indicators to find out whether these indicators have been met or not. The results of this study indicate that in general the application of inventory accounting information systems at PT. PLN (Persero) UP3 Ogan Ilir has been very good.